(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the effects of doses of potassium (K) and foliar sprays of potassium silicate (K2SiO3) associated with increasing doses of nitrogen (N) on morphological characteristics, incidence of common smut and maize grain yield in Terenos, MS, Brazil, in the second crop of 2018/19. The first experiment was in a randomized block design, with five replications, and the treatments were topdressed K2O doses (0, 63, 93, 133 and 173 kg.ha-1). In the second experiment, the design was randomized blocks, in a 4x2+1 factorial scheme and four replications, representing four doses of N (50, 100, 150 and 200 kg.ha-1) in topdress associated with spraying K2SiO3 (0 and 250 g Si.ha-1), with an additional treatment as control. It was used the early hybrid NK 555 VIP3, established with a population of 70000 plants.ha-1. Increasing doses of K2O did not influence the incidence of common smut, the morphological characteristics of the plants and the grain yield, possibly as a function of the level of K previously existing in the soil. There was higher plant height and ear insertion, as well as a lower incidence of common smut in plants that received N+Si, compared to the control. No interaction between doses of N and K2SiO3 was observed for the morphological characteristics evaluated and the incidence of the disease. However, plants fertilized with 50 kg N.ha-1 in topdressing had higher grain yield with K2SiO3 foliar spray.